Chronic Cranial Windows for Long Term Multimodal Neurovascular Imaging in Mice - Kılıç, Kıvılcım; Desjardins, Michèle; Tang, Jianbo; Thunemann, Martin; Sunil, Smrithi; Erdener, Şefik Evren; Postnov, Dmitry D.; Boas, David A.; Devor, Anna (Frontiers in Physiology, 2021)
Chronic cranial windows allow for longitudinal brain imaging experiments in awake, behaving mice. Different imaging technologies have their unique advantages and combining multiple imaging modalities offers measurements of a wide spectrum of neuronal, glial, vascular and metabolic parameters needed for comprehensive investigation of physiological and pathophysiological mechanisms. Here, we detail a suite of surgical techniques for installation of different cranial windows targeted for specific imaging technologies and their combination. Following these techniques and practices will yield higher experimental success and reproducibility of results.